Identidade profissional do docente de licenciatura em Ciências Biológicas da UFS : desvelando os significados de ser professor - Souza, Jobeane França de (2012)
This research aimed to understand how occurs the constitution of teacher professional identity of higher education, based the faculty of the degree course in Biological Sciences, Federal University of Sergipe. For this, we defined the following specific objectives: Identify factors that were remarkable for the constitution of being a profesor today; Check what this the meaning of this university teaching for these profesor; Knowing the views of profesors about the kind of Sciences and Biology teachers they believe are contributing for the formation; Identify the knowledge that profesor mobilize greater recurrence in their professional activities. To this, was chosen a qualitative methodological approach with a phenomenological inspiration. Data collection was conducted through semi-structured interviews with eight profesors, selected according to predetermined criteria. It was concluded that the formation of professional identity of profesor is a continuous process that begins with the pre-professional experience, through the choice of profession, get stronger in the begging formation and in the early years of professional performance and extends to the different spaces of professional performance throughout the teaching career, where each individual continues to produce its own way of being a teacher. It was also found that, in the absence of a collective professional identity, each interviews has built its professional identity and this has not always teaching as the main reference. So, it was found that the construction of professional identity is not a stable and linear. Rather, it involves conflicts, anxieties and contradictions that need to be constantly reconciled in a continuous process of professional socialization. Thus, the institutions of higher education, while professional socialization environment, should provide conditions that help the profesor in building their professional identity.